Heparan sulfate/heparin glycosaminoglycan binding alters inhibitory profile and enhances anticoagulant function of conserved Amblyomma americanum tick saliva serpin 19 - Radulović, Željko M. (Insect Biochem Mol Biol, 2016)
Some serine protease inhibitor (serpin) regulators of essential life pathways bind glycosaminoglycans (GAGs) to enhance inhibitory functions and achieve physiologically relevant rates. This study demonstrates that highly conserved Amblyomma americanum tick saliva serpin 19 (AAS19), a broad-spectrum inhibitor of hemostasis and inflammation system proteases and anticoagulant, can bind heparan sulfate/heparin (HS)GAGs and that this interaction alters its function. Substrate hydrolysis and unpaired t-test analyses revealed that HSGAG binding caused rAAS19 inhibitory activity to: (i) significantly increase against blood clotting factors (f) IIa (thrombin) and fIXa, (ii) significantly reduce against fXa and fXIIa and (iii) moderate to no effect against trypsin, kallikrein, papain, and plasmin. Stoichiometry of inhibition (SI) analyses show that HSGAG binding improved the rAAS19 inhibitory efficiency against thrombin 2.7-4.3 folds as revealed by SI of 13.19 in absence of HSGAGs to 4.83-3.04 in their presence. Our data show that HSGAG binding dramatically enhanced rAAS19 anticoagulant function. In the recalcification time assay, rAAS19 pre-incubated with HSGAGs prior to the assay, delayed plasma clotting by an additional 176-457 s above HSGAGs or rAAS19 alone. Our data suggest that formation of the HSGAGs and rAAS19 complex is important for the observed enhanced anticoagulant effect. Delay of plasma clotting was higher when HSGAGs and rAAS19 were co-incubated to allow complex formation prior to blood clotting assay as opposed to no co-incubation. We have discussed our finding with reference to tick feeding physiology and utility of the rAAS19 in blood clotting disorder therapy.